Mindfulness, Happiness, and Creative Performance in the Public Sector: The Mediating Role of Creative Process Engagement - Safira, Nita; Syarifa, Fadiyani Teja; Ramadhan, Sonia Anita; Amelinda, Chiara Chatlina (Westscience Press, 2025)
Creativity has become increasingly important for public sector organizations as they face complex policy demands, digital transformation, and heightened expectations for accountability and performance. However, creative performance among public employees is often constrained by rigid procedures and highly regulated work environments. This study aims to examine the effects of mindfulness and happiness at work on creative performance, with creative process engagement as a mediating mechanism, within a public sector context. Using a quantitative cross-sectional design, data were collected from 176 employees of the Directorate General of Treasury, Ministry of Finance of the Republic of Indonesia. The data were analyzed using descriptive statistics, multiple linear regression, and mediation analysis. The findings indicate that mindfulness and happiness at work both have positive effects on creative performance. Happiness at work emerges as a stronger direct predictor of creativity, while mindfulness primarily influences creative performance through creative process engagement. Creative process engagement is confirmed as a key mechanism that translates psychological resources into creative outcomes. These results suggest that creativity in public sector organizations is best understood as a process-driven phenomenon, where positive psychological conditions must be accompanied by active engagement in creative work processes. The study offers practical insights for public organizations seeking to foster sustainable creativity under conditions of high regulation and formalization.